Towards a comprehensive knowledge of the open cluster Haffner 9 - Piatti, Andres Eduardo (2017)
We turn our attention to Haffner 9, aMilkyWay open cluster whose previous fundamental parameter estimates are far from being in agreement. In order to provide with accurate estimates, we present high-quality Washington CT1 and Johnson BVI photometry of the cluster field.We put particular care in statistically cleaning the colour-magnitude diagrams (CMDs) from field star contamination, which was found a common source in previous works for the discordant fundamental parameter estimates. The resulting cluster CMD fiducial features were confirmed from a proper motion membership analysis. Haffner 9 is a moderately young object (age ~350 Myr), placed in the Perseus arm - at a heliocentric distance of ~3.2 kpc -, with a lower limit for its present mass of ~160 M ⊙ and of nearly metal solar content. The combination of the cluster structural and fundamental parameters suggest that it is in an advanced stage of internal dynamical evolution, possibly in the phase typical of those with mass segregation in their core regions. However, the cluster still keeps its mass function close to that of the Salpeter's law.